2013
DOI: 10.1063/1.4812976
|View full text |Cite
|
Sign up to set email alerts
|

Condensation and jumping relay of droplets on lotus leaf

Abstract: Dynamic behavior of micro water droplet condensed on a lotus leaf with two-tier roughness is studied. Under laboratory environment, the contact angle of the micro droplet on single micro papilla increases smoothly from 80 deg to 160 deg during the growth of condensed water. The best-known "self-clean" phenomenon, will be lost. A striking observation is the out-of-plane jumping relay of condensed droplets triggered by falling droplets, as well as its sustained speed obtained in continuous jumping relays, enhanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 36 publications
3
138
6
Order By: Relevance
“…However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values. Later, researchers noted that the energy dissipation caused by viscous flow (E vis ) and interface adhesion (E int ) must be considered, [31,[56][57][58][59][60] while gravi tational potential energy may be neglected due to microdrop sizes that are far smaller than the capillary length. Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
“…However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values. Later, researchers noted that the energy dissipation caused by viscous flow (E vis ) and interface adhesion (E int ) must be considered, [31,[56][57][58][59][60] while gravi tational potential energy may be neglected due to microdrop sizes that are far smaller than the capillary length. Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
“…If droplet jumping does not occur again upon droplet return, progressive flooding may initiate at the top surface. This risk is mitigated by the fact that the probability of having an upward trajectory at the top surface tends to zero since most droplets jump at some angle away from the surface 12,21 and the area having a surface normal in the upward direction is infinitesimally small for a radial geometry.…”
Section: Condensate Removalmentioning
confidence: 99%
“…38,55 Upon return, droplets can coalesce again, become larger in size, and impede heat transfer until they either jump again or finally shed due to gravity. [21][22]53 This poses the problem of removing the droplets from the condensing surface at the microscale in order to enhance heat transfer. Naturally, jumping droplets cannot be removed if the condensing surface is oriented upwards (jumping against gravity).…”
Section: Jumping Droplet Condensation Critical Heat Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…When adjacent metastable droplets coalesce, sufficient surface energy is released to overcome the adhesion of the droplet to the surface, resulting in droplet departure from the surface. [24,33,34] This departure can result either in the jumping or random sweeping of mobile droplets off the surface (see the droplets enclosed by the dashed lines in Figure 3b). As a result, many fresh areas on the substrate are exposed and can contribute to the cyclical process of nucleation, coalescence, and departure; a high frequency of surface refreshing, which shifts the distribution of droplets on the surface to smaller sizes, will lead to high heat transfer coefficients in dropwise condensation.…”
mentioning
confidence: 99%